Histological analysis of failed submucosa patches in congenital cardiac surgery. (July 2019) - Heinisch, Paul Philipp; Banz, Yara; Langhammer, Bettina; Stocker, Evelyn; Erdoes, Gabor; Hutter, Damian; Carrel, Thierry; Kadner, Alexander
Objective: Porcine small intestinal submucosa extracellular matrix is a biological substitute used in cardiovascular surgery to correct congenital heart defects. Previous studies with this material have shown satisfactory results. In contrast, there are singular reports of patch-associated complications with CorMatrix small intestinal submucosa extracellular matrix. We report the histopathological findings of explanted extracellular matrix patches that were removed because of early failure in patients with congenital heart defects. Methods: Explanted patch materials from 4 patients (aged 9 months to 41 years), who underwent reoperation due to early patch failure, were analyzed. Initial surgery comprised one aortic valve reconstruction, one pulmonary valve reconstruction, one atrioventricular septal defect repair, and one aortic arch enlargement. The interval between operations ranged from 69 to 553 days. Results: Residual extracellular matrix patch material was evident at explantation in all cases and presented as a structured eosinophilic and anucleate specimen. In two cases, a local focus of scarring and pseudocartilaginous transformation with evidence of calcification was found. There was no evidence of absorption of patch material in any case, nor repopulation by organized tissue formation. Conclusions: Histologic examination of explanted extracellular matrix patches showed no evidence of resorption or relevant repopulation with resident cells nor formation of functional tissue structures. In contrast, a mixed chronic inflammatory infiltration, early signs of calcification, and scarring as well as focal pseudocartilaginous transformation were found. Considering recent reports, close follow-up of patients with extracellular matrix patches is recommended to evaluate the performance of this novel material and detect potential problems.